2020
DOI: 10.1007/s12250-020-00250-1
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying Formulations Increased the Adenovirus and Poxvirus Vaccine Storage Times and Antigen Stabilities

Abstract: Successful vaccines induce specific immune responses and protect against various viral and bacterial infections. Noninactivated vaccines, especially viral vector vaccines such as adenovirus and poxvirus vaccines, dominate the vaccine market because their viral particles are able to replicate and proliferate in vivo and produce lasting immunity in a manner similar to natural infection. One challenge of human and livestock vaccination is vaccine stability related to the antigenicity and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…41,[69][70][71][72][73][74][75] Both vaccines are stable over a range of temperatures, which ensures easy storage and distribution, 55,56 and VACV can also be freeze-dried and stored for extended periods at 25 C without significant impact on immunogenicity. 54 In our study, the comparative analysis of humoral and cellular immune responses between TT and MVA demonstrated that TT is far more effective at stimulating neutralizing antibody production and alloreactive T cell responses against the SARS-CoV-2 RBD (Figure 2). Antibody levels were three to four orders of magnitude lower for MVA immunized mice compared with TT and T cell responses were 2-fold lower.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…41,[69][70][71][72][73][74][75] Both vaccines are stable over a range of temperatures, which ensures easy storage and distribution, 55,56 and VACV can also be freeze-dried and stored for extended periods at 25 C without significant impact on immunogenicity. 54 In our study, the comparative analysis of humoral and cellular immune responses between TT and MVA demonstrated that TT is far more effective at stimulating neutralizing antibody production and alloreactive T cell responses against the SARS-CoV-2 RBD (Figure 2). Antibody levels were three to four orders of magnitude lower for MVA immunized mice compared with TT and T cell responses were 2-fold lower.…”
Section: Discussionmentioning
confidence: 59%
“…We investigated the short-term temperature stability of MVA and TT vaccine vectors, which has previously been demonstrated to be stable long-term under a range of temperature conditions. [54][55][56] Both viruses were stored at À80 C, 4 C, and room temperature for 1 week and then active vaccine particles were quantified by plaque assay. Under these conditions, there was no significant drop in titer TT vectors, but replication of MVA was impaired by storage at room temperature (Figure 1G).…”
Section: Characterization Of Poxvirus Vaccine Vectorsmentioning
confidence: 99%
“…The stabilizing efficiency is controlled by 2 factors: 1. concentration of sugars and 2. cool temperature level that freezes germs [24]. Also, there is a method of Freeze-Drying which increases stability of the Adenovirus and Poxvirus vaccine storage times [25] [26]. Still, financial and technological resources are the constraint of vaccine stability, particularly in underdeveloped regions [25].…”
Section: Efficiency Of 43-year Vaccinesmentioning
confidence: 99%
“…Also, there is a method of Freeze-Drying which increases stability of the Adenovirus and Poxvirus vaccine storage times [25] [26]. Still, financial and technological resources are the constraint of vaccine stability, particularly in underdeveloped regions [25]. In extent, public health knowledge can affect preparedness of prevention [27].…”
Section: Efficiency Of 43-year Vaccinesmentioning
confidence: 99%
“…In recent decades, biopharmaceuticals, including peptides, proteins, vaccines, genes, hormones, and enzymes (Sharma et al 2021 ; O’Sullivan et al 2022a , b ) have experienced rapid growth in their production (Chen et al 2021a , b ). Biopharmaceutical drugs have accounted for 35% of all FDA-approved products over the past 16 years (Vass et al 2019 ), and it is projected that by 2025, this market will be worth $395 billion (Guo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%